Vitamin D Deficiency in Professional Football Players during Competitive Season of Italian First Division (Serie A) - Marco Alfonso Perrone; Massimo Pieri; Giuseppe Caminiti; Wahid Ali; Sergio Bernardini; Attilio Parisi; Ferdinando Iellamo; Rosario Barone; Pasquale Farsetti (MDPI AG, 2024)
Background: Data in the literature have demonstrated the crucial role that vitamin D plays in the human organism, and recent studies also emphasize this essential role of vitamin D in athletes. Indeed, vitamin D acts on the skeletal muscles and plays a fundamental role in numerous physiological processes involved in immune function. Many factors such as sun exposure, skin tone, body mass index and chronic illness affect vitamin D levels. The aim of the study is to evaluate vitamin D levels in professional football players in Italy and investigate the variations in vitamin D values in footballers who train at different latitudes. Methods: The study performed is a retrospective observational study analyzing 25-OH vitamin D values in professional football players of the Italian First Division (Serie A). Two teams during the competitive season were selected: team A (latitude of 41° N in southern Italy) and team B (latitude of 45° N in northern Italy). Three time periods were identified and were classified as follows: the first quarter (May, June, July, and August), the second quarter (September, October, November, and December) and the third quarter (January, February, March, and April). The purpose of this was to study the average values of vitamin D during the year corresponding to different levels of sunlight exposure. Each athlete was subjected to at least one sampling during the three quarters of the competitive season. Results: Both vitamin D insufficiency (10.1%) and overt deficiency (1.93%) were found in Italian Serie A players. Insufficient vitamin D values are between 20 ng/mL and 29 ng/mL and overt deficiency values <20 ng/mL. At the same time, the data demonstrated a significant variation in vitamin D values depending on the period of the competitive season and the latitude of the cities of the two teams. In detail, there was no significant difference in the first quarter, while there was a significant increase in vitamin D values in team B in the second and third quarter, at p < 0.01 and p < 0.05, respectively. Conclusions: Latitude and seasons have a significant impact on vitamin D levels. Therefore, it is essential to measure vitamin D in professional football players, especially during the spring and winter months, so as to monitor changes in levels in relation to the season and latitude and evaluate any supplements. Further studies should be performed to evaluate the relationship between vitamin D deficiency and football players' athletic performance.